Four-loop anomalous dimensions for radiative flavour-changing decays - Czakon, M; Haisch, U; Misiak, M (2007)
We evaluate the complete four-loop anomalous dimension matrix that is necessary for determining the effective flavour-changing neutral current couplings q′γ and q′g at the next-to-next-to-leading order in QCD. The resulting (αs2(μb)) correction to the Xsγ branching ratio amounts to around -2.9 for μb ≤ 5 GeV, and -4.4 for μb ≤ 2.5 GeV. © SISSA 2007.